Physical Condition and Its Relationship to the Functional Efficiency of some National Teams for Girls in the Sultanate Of Oman - Majid , AL-Busafi; Murcy, Hala; Mahfudah , AL-Kitani (Journal of Sport Science Technology and Physical Activities, 2025)
In terms of the lack of scientific research that address the state of the players in the national teams in the Sultanate study, and stand on their level and the development of their situation, it came the idea of understand the Physical Condition and its relationship to the functional efficiency of some national teams for girls in the Sultanate of Oman. Descriptive approach was used due to its suitability to the nature of this study. It was selected community sample of girls participating in Omani national teams in the sport (volleyball - Handball - Basketball - athletics), which makes the total sample of (60) female athletes. The results of the study showed that there are significant differences between the average scores of the four measurements in the case of physical variables. The researchers attributed this result to the inhalers and exercises appropriate to the capabilities of the players working to improve the level of fitness, and make them able to perform the activity requirements. One of the main recommendations of this study is the need for some consecutive measurements of the national team players in the Sultanate of Oman through training programs to make sure of the validity of the program to achieve its desired objectives period.